Physical mechanism of intermittency route to aeroelastic flutter. (November 2017) - Venkatramani, J.; Kumar, S. Krishna; Sarkar, Sunetra; Gupta, Sayan
Abstract: Intermittency has been observed in the response of aeroelastic systems in the presence of flow fluctuations. This study focuses on developing an understanding of the physical mechanisms that lead to intermittency in such systems. Specifically, the role of time scales of the input flow fluctuations is investigated. Numerical investigations reveal that flow fluctuations with predominantly long time scales in the pre-flutter regime lead to "on–off" type intermittency. On the other hand, rapid fluctuations constituting of small time scales lead to another qualitatively different intermittency, which is referred to in this paper as "burst" type intermittency. It is further shown that the unsteady wake effects play a crucial role in the burst type intermittency. Measures derived from time series analysis of the aeroelastic response are proposed to identify the different dynamical states quantitatively. Highlights: The role of time scales of flow fluctuations on aeroelastic response is studied. Long time scale fluctuations give rise to "on–off" type intermittency. Fluctuations with short time scales lead to "burst" type intermittency. The role of unsteady wake effects on "burst" intermittency is demonstrated. Measures from time series analysis used to quantify different dynamical responses.